2019
DOI: 10.1021/acschembio.8b00849
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Mycobacterium tuberculosis DosRST Signaling by Targeting Response Regulator DNA Binding and Sensor Kinase Heme

Abstract: Mycobacterium tuberculosis (Mtb) possesses a two-component regulatory system, DosRST, that enables Mtb to sense host immune cues and establish a state of nonreplicating persistence (NRP). NRP bacteria are tolerant to several antimycobacterial drugs in vitro and are thought to play a role in the long course of tuberculosis therapy. Previously, we reported the discovery of six novel chemical inhibitors of DosRST, named HC101A–106A, from a whole cell, reporter-based phenotypic high throughput screen. Here, we rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…Although originally for Gram-positive bacteria, oxazolidinones—linezolid and its derivatives—are in many clinical trials, with linezolid already approved for use in TB [ 22 ]. In addition, the antiparasitic artemisinin is currently receiving a lot of attention from the research community for its ability to disrupt signalling that regulates persistence in M. tuberculosis [ 23 , 24 , 25 , 26 ].…”
Section: The Prospect Of Repurposingmentioning
confidence: 99%
“…Although originally for Gram-positive bacteria, oxazolidinones—linezolid and its derivatives—are in many clinical trials, with linezolid already approved for use in TB [ 22 ]. In addition, the antiparasitic artemisinin is currently receiving a lot of attention from the research community for its ability to disrupt signalling that regulates persistence in M. tuberculosis [ 23 , 24 , 25 , 26 ].…”
Section: The Prospect Of Repurposingmentioning
confidence: 99%
“…Targeting TCS has been an active area of research to translate studies of bacterial pathogenesis into new classes of antivirulence antibiotics [ 9 , 10 , 72 ]. A variety of approaches have been employed to discover TCS inhibitors, including whole cell reporter-based high-throughput screens (HTS) [ 45 , 64 , 65 , 73 ]; phenotypic HTS targeting TCS-dependent responses [ 74 ]; target-based biochemical assays focused on inhibition of bacterial histidine kinase activity by small molecules [ 75–77 ] or response regulator mimetic peptides [ 78 , 79 ]; or inhibition of response regulator DNA binding [ 80 , 81 ]. These approaches have generated several new compounds that are in preclinical development as novel antivirulence therapies.…”
Section: Molecules Targeting the Dosrst Pathwaymentioning
confidence: 99%
“…Mechanism of action studies were initially carried out on three of the inhibitors: artemisinin, HC102A and HC103A ( Figure 2 ). RNAseq transcriptional profiling experiments showed that the compounds inhibit the DosR regulon when compared with a dosR mutant control strain [ 64 , 65 ]. Notably, the triacylglycerol (TAG) synthase gene tgs1 was repressed and treatment with the artemisinin, HC102, HC103 significnatly reduced TAG accumulation.…”
Section: Molecules Targeting the Dosrst Pathwaymentioning
confidence: 99%
“…As the DosR/DosT regulon is important for adaptation and survival of M. tuberculosis under hypoxic conditions, it might be a good target for new therapeutics. One promising inhibitor is artemisinin that disables the heme-base DosT sensor kinase [136]; further inhibitors with multiple distinct mechanisms have been identified [137]. is enhanced, which leads to increased glucose uptake into the cell.…”
Section: Bacterial Oxygen Sensingmentioning
confidence: 99%